Bimodal networks as hypothesis generators: Towards a reticular analysis applied to population censuses of the Puna de Jujuy, Argentina, 18th century - Fernández, Federico; Peña Aguilera, Daniela (AWARI, 2024)
This text delineates the methodology for transforming population census data into bimodal matrices and networks. The data analyzed is derived from registers and censuses about native groups in the Puna region of Jujuy after the eighteenth century. Considering the particulars of the information in these historical documents, it was imperative to establish the connections (or edges) that linked each individual with the administrative and ecclesiastical categories imposed on the local populations through the colonial regime. The results permit the measurement and visualization of the information recorded under the logic of a colonial administration. However, the networking of this information enables the construction of research questions and hypotheses focused on the relational reconstruction of the hierarchical and power processes that arose between these local populations and the impositions of a Spanish elite responsible for territorial administration.